The Component Of Lesson Plan On Classroom Management - Firnando Sabetra; Ambiyar; Ishak Aziz (International Journal Of Humanities Education and Social Sciences (IJHESS), 2021)
The present study has been conducted to identify and understand the component of the lesson plan on classroom management. The method used in this study uses a library method or approach (library research). Data obtained through observation and literature study. The results showed that the lesson plan as a well-organized planning of a lesson for estimating or projecting what will be done with the students in learning during classroom activities. The lesson plan must consist of ten components. These components of a lesson plan are: identity of school class, identity of the lesson, core competence, basic competences and indicators of competent achievement, objectives, materials, methods of teaching, media and resources, teaching activities and assessments. Planning  lessons  and  setting  goals  from  the  begging  would  help  the  students  to  gather  their  thoughts  about  the lesson  before class. So, the teacher should know how to manage the classroom. The classroom management is the relation between the teacher’s ability and student’s behavior to establish an appropriate classroom learning and teaching.